Development of Domino Card as Math Learning Media to train students’ Conceptual understanding - Arief Aulia Rahman; Yuli Amalia (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
This study aims to describe the validity, practicality and effectiveness of domino card media that will be developed to train students' understanding of concepts in learning mathematics, the instruments used are tests, questionnaires and interview sheets. The research subjects were grade VII of Junior High School at Meulaboh. This research was carried out through two stages, namely the first stage of developing domino card media using the Four-D model, and the second stage testing the domino card media developed to see its effectiveness. From the results of the trial obtained: 1) domino card media developed valid with a value of 77.5 good categories, 2) the practicality of domino cards seen from student response questionnaires with a value of 88.1% good category. And c) the effectiveness of domino card media in terms of student learning classical completeness, namely 72.7% is complete.